Black Cumin Seed Extract as Copper Corrosion Inhibitor in H2SO4 1M: An Experimental and Theoretical Study - Elsa, Putri; Hamdiani, Saprini; Yuanita, Emmy; Hadisaputra, Saprizal (Postgraduate, University of Mataram, 2024)
Experimental corrosion tests and theoretical calculation were conduct to investigate the corrosion inhibition mechanism of black cumin seed extract for copper in 1 M H2SO4 solution. Electrochemical testing using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) method showed that BCS adsorbed to form a protective layer on the copper surface with high inhibition efficiency at 500 ppm concentration (73,35%). Increasing the BCS concentration up to 500 ppm causes the charge transfer resistance increase in the EIS measurement, while the corrosion current density measured by PDP decreases. The values of charge transfer resistance and corrosion current density at 500 ppm BCS are respectively 3687 .cm2 and 2.86 μA.cm-2. The BCS is a mixed inhibitor (anodic and cathodic) that adsorbs physically on the copper surface and obey the Langmuir isothermal adsorption model. Quantum chemical calculation and molecular dynamic simulation show that the studied BCS molecules adsorb strongly on the copper surface with parallel orientation mode. The methyl linoleate (MLIN) molecules from BCS produce the most stable adsorption energy of the other studied compound molecules as a result of molecular dynamic simulation.